The effect of short circuits and flame temperature modes on the change in the microstructure of copper in automotive wiring. (June 2022) - Gudym, Vasyl'; Mykhalichko, Borys; Nazarovets, Oleg; Gavryliuk, Andrii
Graphical abstract: Highlights: Vehicular fire causes were investigated by analyzing the copper microstructure of car wiring. The copper microstructure was studied by an OM and a SEM equipped with EDX spectrometer. New investigation approaches of the causes of vehicular fires were formulated. Abstract: The purpose of the work is to investigate the causes of vehicle ignition by analyzing the microstructure of copper conductive elements of automotive wiring. This study considers the three most likely vehicle fire scenarios. According to the first scenario, a fire occurs due to overheating of the automotive wiring by short circuit currents. In the second scenario, car fires result from direct exposure to an open flame. In the third scenario, vehicle fires are due to the combined effects of short circuits and open flames. These three scenarios affect the microstructure of copper conductive automotive wiring elements in different ways. Microstructural analysis of copper wires exposed to the temperature conditions of these three fire scenarios was carried out using an optical microscope (OM) and a scanning electron microscope (SEM) equipped with an energy dispersive X-ray (EDX) spectrometer. It has been disclosed that when exposed to an open flame on a copper wire, the fine-grained microstructure of the original copper wire turns into a coarse-grained one. The impact of an electric arc caused by a short circuit can instantly melt copper wires. As a result, local spherical inclusions (beads and pits) appear on the surface of the copper wire, and grains of the dendritic structure are formed in its surface layer. The impact of an open flame on already short-circuited copper wires transforms their fine-grained microstructure containing local spherical inclusions into a kind of coarse-grained microstructure with clear boundaries between grains consisting of copper(II) oxide. The study of the microstructure of copper wires taken from a burned-out car should form the basis for studying the causes of car fires.